Do Japanese students overestimate or underestimate their knowledge of English loanwords more than non-loanwords on yes-no vocabulary tests? - Raymond Stubbe (Vocabulary Learning and Instruction)
English loanwords (LWs), gairaigo in Japanese, make up a much greater percentage of the Japanese language than many university English teachers realize, especially if their native language is not Japanese. Unfortunately, a gairaigo bias exists which has made these LWs unpopular amongst teachers and researchers. The aim of this study is to compare student over-estimation and under-estimation of their knowledge of English LWs on yes-no vocabulary tests with an equal number of non-loanwords (NLWs). Undergraduate students from four Japanese universities (n 455) took two vocabulary tests of their receptive and passive recall knowledge of LWs and NLWs. Six LWs and six NLWs from each of the eight JACET 8000 levels were tested in a selfreport yes-no test followed by a passive recall translation test (English to Japanese) of the same 96 items. Overall, over-estimation rates were nearly equal at 24.6% for LWs and 25.8% for NLWs. Additionally, overestimation was more prevalent for NLWs at the higher three frequency levels (1K-3K), nearly equal with LWs at the 4K level and then more prevalent for the LWs at the lower four frequency levels (5K-8K), suggesting that student knowledge of NLWs is weak even at the higher frequency levels. Under-estimation, on the other hand, was much more prevalent for LWs (4.4% versus 0.7%). Six of the 48 LWs actually had higher passive recall test scores than yes-no test scores. These results suggest that although students do not over-estimate their knowledge of LWs more than NLWs on yes-no vocabulary tests, they do underestimate their LW knowledge much more than NLWs.